Cross-Cultural Analysis: Leadership in Cross-Cultural Management - Junaidi Hendro (SAJMR : Southeast Asian Journal of Management and Research, 2024)
Leadership in cross-cultural management has become increasingly important in the era of globalization. This article analyzes how cultural differences influence leadership styles and management effectiveness in international organizations. By reviewing existing literature and conducting empirical research, this study explores the challenges faced by cross-cultural leaders and the solutions that can be applied to address these issues. The research findings indicate that a deep understanding of cultural differences and the adaptation of leadership styles are key to success in cross-cultural management. Additionally, this article presents various practical strategies that leaders can implement to enhance the effectiveness of cross-cultural management, including intercultural training and the development of communication skills